2018
DOI: 10.1186/s12905-018-0590-4
|View full text |Cite
|
Sign up to set email alerts
|

An update on obesity research pattern among adults in Malaysia: a scoping review

Abstract: BackgroundObesity is a global health burden in the non-communicable diseases and much efforts have been implemented in the past decade in response to the rise of obesity prevalence among the Malaysian population. These include the development of the national policies, health programmes and research activities. The main aim of the scoping review was to identify obesity research pattern among adults in Malaysia in terms of the scopes, topics and the research designs.MethodsThe scoping review was conducted based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Besides, visceral fat is regional fat depots that are located inside the abdominal cavity and stored around the abdominal organs, can be estimated accurately by magnetic resonance imaging, computed tomography, or dual-energy X-ray absorptiometry, and has also been utilized to evaluate visceral fat ( 25 ). Previous observational studies revealed that obesity was closely related to all-cause mortality ( 14 , 26 , 27 ). A pooled analysis of 20 prospective studies showed that extreme obesity (BMI 40.0–59.9 kg/m 2 ) may shorten life expectancy by up to 14 years ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, visceral fat is regional fat depots that are located inside the abdominal cavity and stored around the abdominal organs, can be estimated accurately by magnetic resonance imaging, computed tomography, or dual-energy X-ray absorptiometry, and has also been utilized to evaluate visceral fat ( 25 ). Previous observational studies revealed that obesity was closely related to all-cause mortality ( 14 , 26 , 27 ). A pooled analysis of 20 prospective studies showed that extreme obesity (BMI 40.0–59.9 kg/m 2 ) may shorten life expectancy by up to 14 years ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Between 1996 [23] and 2015 [24], the prevalence of obesity among adults in Malaysia showed a four-fold increase, surging from 4.4% to 17.7%. In 2011 and 2015, the prevalence of being overweight among Malaysian adults was 29.4% and 30%, respectively, while during the same period, obesity accounted for 15.1% and 17.7%, respectively [25]. In the National Health and Morbidity Survey (NHMS) 2019, the current prevalence of obesity among Malaysian adults was 19.7% [26].…”
Section: Introductionmentioning
confidence: 99%
“…Pahang, Pulau Pinang, Terengganu, and Sabah showed the lowest rates of obesity (15.7%-18.6%) in comparison to other states in Malaysia [26]. Between 2011 and 2019, there was an alarming rate of increase in obesity among adults in Selangor (17.1% and 19.3%) [26], a highly populated state in Malaysia [25]. As well as geographic patterning, there are ethnic disparities in the prevalence of obesity among Malaysian adults.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the latest National Health and Morbidity Survey (NHMS 2016) suggested that the prevalence of MetS risk factors has increased rapidly in recent years [2], while a few studies showed a remarkably high prevalence of MetS clustering among Malaysians [3]. This is partly a result of rapid socio-economic development, which comes at the expense of healthy diet and active lifestyle [4,5].…”
Section: Introductionmentioning
confidence: 99%